Dual Control System for Virtual Protection of a Remote UAV Experiment - Samuelsen, Dag A. H.; Graven, Olaf H. (International Journal of Online and Biomedical Engineering (iJOE), 2012)
The topic of this paper is the utilisation of a strategy with a dual control system for the prevention of damage on laboratory equipment used in a remote laboratory. One control system is implemented before the laboratory is deployed and is responsible for damage control and can override the second control system that is programmed by the user of the remote laboratory and is fully configurable. The laboratory is used for verification of control algorithms for quad rotor helicopters through practical experiments. The damage control strategy should not limit or impede the natural movement of the equipment as long as the behaviour is kept within predefined limits. The nature of the system to be controlled, exclude the use of physical constraints that are normally used for damage control, as these in some way or another will impede or limit the movement of the helicopter.